The structural, electrical, and photoelectrical properties of Al/Cu2CdSnS4 chalcogenide film/p-Si Schottky-type photodiode - Al-Sehemi, Abdullah G.; Tataroglu, A.; Dere, Aysegul; Karabulut, Abdulkerim; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2023)
The Cu2CdSnS4 (CCTS) film has been prepared using the hydrothermal approach and deposited on the p-type silicon wafer by the use of the sol-gel technique. Then, the CCTS based Al/Cu2CdSnS4 (CCTS)/p-Si/Al photodiode was produced. The prepared CCTS film was analyzed using various characterization methods such as energy-dispersive X-ray (EDX or EDS), scanning electron microscopy, and ultraviolet-visible (UV-Vis) spectroscopy. Optoelectronic and electronic attributes of the generated photodiode were investigated under the solar light and frequency conditions. The obtained data from the current measurements based on illumination intensity showed that the generated diode exhibits a photovoltaic and photoconductive behavior. In addition, it is found that the conductance and capacitance features of the diode were quite sensitive to frequency. The obtained outcomes indicated that the produced structure could be used in optoelectronic technology, especially in photodiode and solar cell applications.
Keywords: Barrier Height Modification; Cu2Cdsns4 Thin-Films; Capacitance-Voltage; Interface Structure; Temperature; Frequency; Transport; Nanostructure; Mechanisms; Deposition